2019
DOI: 10.13057/biofar/f170102
|View full text |Cite
|
Sign up to set email alerts
|

The potential of white-oyster mushroom (Pleurotus ostreatus) as antimicrobial and natural antioxidant

Abstract: Abstract. Egra S, Kusuma IW, Arung ET, Kuspradini H. 2018. The potential of white-oyster mushroom (Pleurotus ostreatus) as antimicrobial and natural antioxidant. Biofarmasi J Nat Prod Biochem 16: 17-23. White-oyster mushroom (Pleurotus ostreatus) is a favorite meal in Indonesia. Previously this fungus was known as a useless plant, but after the nutrition is known, everything changes. People tried to cultivate it because the nutrients contents are very good for body health. Therefore, to support this added valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 17 publications
1
12
0
1
Order By: Relevance
“…Results of study revealed that the ethanolic extract was more effective than aqueous extract and this results in agreement with the results of Eun-Ji, etal., 7 who found that the ethanolic extract ofPleurotuseryngiiwere the most effective against tested microbes and contain The results also agree with Egra, et al, 22 who found the antifungal activity ofoyster mushroom against Candida albicans and found that ethanolic extract affect the growth of the fungus and the effect increased with the increasing of concentration and the inhibition zones ranged between 9.3 to 10.8mm .…”
Section: Discussionsupporting
confidence: 77%
“…Results of study revealed that the ethanolic extract was more effective than aqueous extract and this results in agreement with the results of Eun-Ji, etal., 7 who found that the ethanolic extract ofPleurotuseryngiiwere the most effective against tested microbes and contain The results also agree with Egra, et al, 22 who found the antifungal activity ofoyster mushroom against Candida albicans and found that ethanolic extract affect the growth of the fungus and the effect increased with the increasing of concentration and the inhibition zones ranged between 9.3 to 10.8mm .…”
Section: Discussionsupporting
confidence: 77%
“…Extracts of fruiting body powder from P. ostreatus , showed antimicrobial activity against C. albicans ; the result of the assay showed the formation of barriers on the extract concentration zone of 10.8 mm width [ 72 ]. A comparative study of Pleurotus spp.…”
Section: Bioactive Compounds and Their Activitymentioning
confidence: 99%
“…Oyster mushrooms are also a good source of total dietary fibre (35.6 g/100 g) with 35.4 g/100 g of insoluble dietary fibre and 0.2 g/100 g of soluble dietary fibre [19]. The potential of white oyster mushroom as a natural antimicrobial and antioxidant which is a favourite food in Indonesia because it is easy to find [28].…”
Section: Resultsmentioning
confidence: 99%